Linguistic Maintenance of the Database of Meronyms of the National Corpus of the Uzbek Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is based on the study of the phenomenon of meronymy in linguistics and that it is exactly the same as the phenomenon of partonymy. Linguists have commented on their research on meronymy.